2016
DOI: 10.1021/acs.joc.5b02735
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent Strategy for the Synthesis of Prostaglandin E2 Methyl Ester under Anion Relay Chelation Control

Abstract: Starting with four components, the enantioselective synthesis of prostaglandin E2 methyl ester has been achieved through a highly stereoselective heteroatom-directed conjugate addition reaction and cyclopentanone ring cyclization as the key steps. This asymmetric strategy includes (i) an asymmetric Reformatsky reaction; (ii) conjugate addition of a chiral vinyllithium reagent; (iii) cyclization to form a sulfonylated cyclopentanone in one-pot; followed by (iv) allylation of the side chain. Four carbon-carbon b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…More recently, excellent results were also reported by Isobe et al for a diastereoselective SmI 2 -mediated Reformatsky reaction constituting the key step of a highly economical total synthesis of prostaglandin E 2 methyl ester [ 23 ]. As shown in Scheme 7 , the reaction occurred between achiral aldehyde 17 and chiral oxazolidinone 18 in the presence of SmI 2 in THF at −78 °C to give the corresponding chiral secondary alcohol 19 in high yield (88%) combined with excellent diastereoselectivity (>95% de).…”
Section: Reviewmentioning
confidence: 99%
“…More recently, excellent results were also reported by Isobe et al for a diastereoselective SmI 2 -mediated Reformatsky reaction constituting the key step of a highly economical total synthesis of prostaglandin E 2 methyl ester [ 23 ]. As shown in Scheme 7 , the reaction occurred between achiral aldehyde 17 and chiral oxazolidinone 18 in the presence of SmI 2 in THF at −78 °C to give the corresponding chiral secondary alcohol 19 in high yield (88%) combined with excellent diastereoselectivity (>95% de).…”
Section: Reviewmentioning
confidence: 99%
“…Corey’s synthesis was later commercialized with the introduction of very cost-effective synthesis of Corey lactone by Tomoskozi et al in 1976, which is still used today in various improved formats. , In 2012, Aggarwal group described remarkably shortened seven-step synthesis of prostaglandin PGF 2α . This achievement has started a renaissance in this synthesis field with several groups reporting elegant and short access to various prostanoids . With respect to potential industrial application of newly reported routes, it is instructive to compare cost effectiveness of latest reported syntheses of commercially most successful prostanoid drug–latanoprost.…”
Section: Introductionmentioning
confidence: 99%
“…Multicomponent reactions involving cascade processes provide powerful strategies for the total synthesis of natural products and synthetically useful building blocks. , Among them, isocyanide-based multicomponent reactions are particularly important. , Recently, 2-isocyanoethylindoles, bearing a nucleophilic isocyanide at the C3-position of the indoles, have been used as precursors for the rapid construction of spiroindolines . Because the chemoselective synthesis of spiroindolines and pyrroles have been achieved by using a 2-isocyanoethylindole-based domino reaction, , a number of chemo- and enantioselective synthetic methods have been established for the dearomatization of 2-isocyanoethylindoles to afford spiroindolines.…”
mentioning
confidence: 99%